Habitat fragmentation, climate change, and inbreeding in plants. - Leimu, R; Vergeer, P; Angeloni, F; Ouborg, N (2010)
Habitat fragmentation and climate change are recognized as major threats to biodiversity. The major challenge for present day plant populations is how to adapt and cope with altered abiotic and biotic environments caused by climate change, when at the same time adaptive and evolutionary potential is decreased as habitat fragmentation reduces genetic variation and increases inbreeding. Although the ecological and evolutionary effects of fragmentation and climate change have been investigated separately, their combined effects remained largely unexplored. In this review, we will discuss the individual and joint effects of habitat fragmentation and climate change on plants and how the abilities and ways in which plants can respond and cope with climate change may be compromised due to habitat fragmentation.